Financial Inclusion and Virtual Bank in the Era of Digitalisation: A Regulatory Case Study in Hong Kong - Sau-Wai Law (SocioEconomic Challenges)
Implicit in the promise of virtual banks is the mission of promoting financial inclusion in Hong Kong, through offering increased accessibility and brand-new customer experiences through the internet which are said to be easier, more personalised and customer-centered. Nevertheless, while regulators encourage using technological solutions to reduce barriers to access and friction, there is a need to strike a balance between promoting technological innovations, protecting customers, and enhancing the returns to investors. Through the content analysis of the recent speeches and guidelines from Hong Kong Monetary Authority and the financial inclusion report from the United Kingdom, it is observed that the regulation of virtual banks in Hong Kong tends to focus predominately on promoting technological innovations. This is unlikely to be sufficient to replicate the trust and confidence in the traditional banking environments due to the lack of consideration to incorporate human factors between banks and clients. This paper articulates the importance of improving the following three areas which could be incorporated into future amendments to future regulatory guidelines: First is to review and accommodate the differences in the bank-customer relationship under the new interaction model. Second is to enhance transparency and disclosure of the technology involved in virtual bank operation. Third is to provide greater assistance to customers to improve their comprehensiveness of the increasing complexity of bank operation, particularly for those who do not have high financial literacy and those who might be discouraged from making an enquiry due to lack of human interaction with the banks. These would improve accessibility and make a meaningful impact to financial inclusion through the launch of virtual banks in Hong Kong.